(untitled) (Research, Society and Development, 2020)
The coronavirus, a genre of the Coronaviridae Family, are known to be a enveloped vírus with a large and positive RNA genome. Among the main routes of coronavirus transmission are: the direct one, through coughing, sneezing and stray and transmission through contact with oral, nasal and eye mucosa. Although the presence of neurological symptoms in the first patients infected with COVID-19 has been of low scale, in the past few days, reports of neurological cases are more frequent, in addition to those on the medium and long term consequences of the pandemic in the Central Nervous System (CNS) and/or impacts on neurological diseases. Thus, this research aimed to describe the neurological complications in patients infected with the new coronavirus. It is an integrative literature review, of an exploratory nature, with a qualitative approach. To carry out this study, the following databases were consulted: MEDLINE, Google Scholar and SCIELO. The descriptors were used in an associated way: Neurological Complications, Neurology, COVID-19 and Coronavirus Infections. Initially, articles that addressed the proposed theme were considered. To compose the basis for the discussion of this study, a total of 9 articles were retrieved by the search strategies, which were fully analyzed and discussed. Neurological symptoms were classified into three categories: symptoms or diseases of the Central Nervous System, such as headache, dizziness, impaired consciousness, ataxia, acute cerebrovascular disease and epilepsy, symptoms of the Peripheral Nervous System, such as hypogeusia, hyposmia, hypopsia and neuralgia , and musculoskeletal symptoms.